Graduate Student-Athletes: An Examination of Identity Roles and Transition - Amanda Blakewood Pascale; Elizabeth Gregg; Andrea Buenano (University of Kansas Libraries, 2021)
Increasingly, student athletes are enrolling in graduate programs with remaining athletic eligibility. From identity role conflict and transition theory approaches, this study examines how graduate student athletes develop by negotiating their identities as both graduate students and as athletes. Implications for collegiate administrators, coaches, and faculty who seek to support graduate student success and transition out of sport are discussed.